The Preamble Of The Constitution As A Constitutional Touchstone: Indonesian Practices - Deden Rafi Syafiq Rabbani; Ali Abdurahman; Mei Susanto (Arena Hukum, 2022)
This paper aims to provide an analysis of two important things: First, the conception and use of the preamble to the constitution can be a constitutional touchstone. Second, the use of the preamble to the 1945 Constitution of the Republic of Indonesia as a constitutional touchstone in practice in Indonesia. This normative juridical research uses statutory approach, conceptual approach and case approach. The result is that as a constitutional touchstone, not only the values ​​in the preamble to the constitution are reflected in every constitutional provision, but are also used as a basis for constitutional interpretation, as well as a tool to test the validity of the law in resolving conflicting norms. Furthermore, in Indonesia the use of the Preamble to the 1945 Constitution as a constitutional touchstone is related to the legal position and status of the Preamble to the 1945 NRI Constitution as an integral part of the constitution as well as a foundation in establishing a constitution. The preamble to the 1945 Constitution is often used as a source of constitutional rights in the practice of judicial review at the Constitutional Court, as well as a tool in testing the legal validity of a statute.